The effect of floor joists on the elastic and inelastic behavior of R.C frames. (1st October 2019) - Montuori, Rosario; Nastri, Elide; Palese, Maria Ilenia; Piluso, Vincenzo
Highlights: A relationship to consider both the stiffness and the strength is proposed. The formulation has been validated by parametric analyses both elastic and inelastic. The formulation reliability is confirmed by both linear analyses and pushover results. Abstract: The influence of floor joists of Reinforced Concrete buildings can deeply affect the structural response against horizontal loading. However, this contribution is generally neglected. Reinforced Concrete (RC) buildings, designed with outdated criteria, frequently have a framed structure where the internal beams parallel to the floor joists could be missing, and the linking is demanded to the joists only. Their contribution in terms of lateral stiffness and resistance can be relevant when a seismic event also occurs in the presence of linking beams parallel to floor joists. Besides, codes do not provide any design rule to consider the joists contribution. For these reasons, the primary goal of this paper is to find a theoretical relationship, suitable for both new and existing buildings, allowing to account for both the stiffness and the resistance due to the presence of joists. To this scope, linear and non-linear analyses on a large number of multi-storey RC frames have been performed.